Academic research and artistic practice in Chain Reaction: Methodology on Two Levels - Perez, Elena (Nordic Journal of Art & Research, 2014)
This article describes the ways in which an academic method of research was combined with an artistic method in the production of Chain Reaction, a creative project developed by the author as part of her PhD program, using the methodology of practice-based research. The article describes the research design, and displays the negotiation between two different questions throughout the project—artistic and academic—by analysing two significant moments: devising artistic work with collaborators and working with theory. It is then argued that the cooperation between artistic practice and academic research enriches each field while simultaneously creating a strong form of cultural practice with both aesthetic and epistemological elements.